2009
DOI: 10.1177/155005940904000308
|View full text |Cite
|
Sign up to set email alerts
|

Visual Dysfunction and Computational Sleep Depth Changes in Obstructive Sleep Apnea Syndrome

Abstract: The aims of this study are to clarify whether patients with obstructive sleep apnea syndrome (OSAS) have a decline in verbally or visually-based cognitive abilities and whether the possible decline is related to particular sleep depth changes. In addition, the effect of continuous positive airway pressure (CPAP) on the possible changes is investigated. Fifteen OSAS patients and 15 healthy controls joined two full-night polysomnographies, including a computational measure of deep sleep percentage (DS%) bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…The research by Twigg et al [ 62 ] has shown that verbal but not visual memory was impaired in OSA patients. Yet, it was found that OSA patients have mild visual cognitive dysfunction [ 63 ]. And a recent meta-analysis which included 42 researches revealed that verbal episodic memory and visuospatial episodic memory mainly representing the domain of immediate and delayed recall were disturbed in OSA in comparison to healthy group [ 64 ].…”
Section: Neurocognitive Dysfunction In Osasmentioning
confidence: 99%
“…The research by Twigg et al [ 62 ] has shown that verbal but not visual memory was impaired in OSA patients. Yet, it was found that OSA patients have mild visual cognitive dysfunction [ 63 ]. And a recent meta-analysis which included 42 researches revealed that verbal episodic memory and visuospatial episodic memory mainly representing the domain of immediate and delayed recall were disturbed in OSA in comparison to healthy group [ 64 ].…”
Section: Neurocognitive Dysfunction In Osasmentioning
confidence: 99%
“…daytime sleepiness and attention or vigilance dysfunction [25][26][27][28][29][30][31] . Studies using sleep EEG derived from PSG have documented significant differences in spectral power or sleep spindles during non-rapid eye movement (NREM) sleep between patients with OSA and controls [32][33][34][35] . Although previous spectral analysis studies have investigated EEG and oximetric spectral features to improve OSA detection 21 , little is known about differences in sleep qEEG between patients with SS and those with OSA.…”
mentioning
confidence: 99%
“…They also have deeper sleep than OSA patients in all EEG derivations. Moreover, they present with lighter sleep than healthy controls in the same EEG derivations that show a reduced amount of slow EEG frequencies in OSA patients with six months of CPAP treatment (Saunamaki et al, 2009). Poor quality sleep might explain some of the subjective symptoms of PPO patients.…”
mentioning
confidence: 87%